JOINT EFFECT OF GROWTH STIMULATOR AND COHERENT EMI EHF WITH LOW INTENSITY ON TOTAL PEROXIDASE ACTIVITY IN AMARANTH (AMARANTHUS L.) GERM CELLS (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
The influence of EMI EHF as well as the joint effect of physical and chemical factors, EMI EHF and C-2 growth stimulator, influences on total peroxidase activity of Amaranth (Amaranthus L.) germs have been investigated. It has been shown that low intensity irradiation of Amaranthus L. seeds by EMI EHF influences on germs’ oxidation processes intensity. The joint effect of stimulator and external physical field results in increasing of influence of external environment factors on biological system.
Keywords: EMI EHF; C-2 growth stimulator; peroxidase activity; germs; joint effect